2006
DOI: 10.1186/1472-6882-6-39
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antibacterial activity of some plant essential oils

Abstract: Background: To evaluate the antibacterial activity of 21 plant essential oils against six bacterial species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

29
520
11
10

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 777 publications
(570 citation statements)
references
References 33 publications
29
520
11
10
Order By: Relevance
“…In contrast, linalool and terpin-4-ol were more effective against Gram-negative bacteria than Gram-positive strains. There are many reports describing the antimicrobial activities of essential oils [26][27][28][29][30].…”
Section: Discussion When We Compared the Isoprenoids' Effects Againstmentioning
confidence: 99%
“…In contrast, linalool and terpin-4-ol were more effective against Gram-negative bacteria than Gram-positive strains. There are many reports describing the antimicrobial activities of essential oils [26][27][28][29][30].…”
Section: Discussion When We Compared the Isoprenoids' Effects Againstmentioning
confidence: 99%
“…For instance, eugenol (2-methoxy-4-2-propenyl phenol), the phenolic component of clove is known to possess antibacterial activity (Burt 2004) and clove is reported to posses highest total phenolic constituents (141 mg/g) compared to other spices like cumin and black mustard. In vitro antimicrobial activity of some plant essential oils on several Gram positive and Gram negative bacteria is reported (Sreenivasan et al 2006). Inhibitory effect of clove on several spoilage and toxigenic molds is well established (Rajkumar and Berwal 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Terpenoids also play key roles in the clinical industry (Singh and Sharma 2015). Prabuseenivasan et al (2006) proved that cinnamon oil showed a broad range of activity against Pseudomonas aeruginosa. Moreover, the terpene composition can vary markedly among different species.…”
Section: Volatile Terpenoids: Impact On the Agroecosystemmentioning
confidence: 99%